2013
DOI: 10.1073/pnas.1310766110
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment is associated with altered fear circuitry and increased internalizing symptoms by late adolescence

Abstract: Maltreatment during childhood is a major risk factor for anxiety and depression, which are major public health problems. However, the underlying brain mechanism linking maltreatment and internalizing disorders remains poorly understood. Maltreatment may alter the activation of fear circuitry, but little is known about its impact on the connectivity of this circuitry in adolescence and whether such brain changes actually lead to internalizing symptoms. We examined the associations between experiences of maltrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
314
11
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(372 citation statements)
references
References 58 publications
35
314
11
3
Order By: Relevance
“…At a first glance, this seems inconsistent with previous findings that ELS is associated with decreased amygdala-prefrontal FC during resting state (Burghy et al, 2012;Fan et al, 2014;Herringa et al, 2013). However, it is important to emphasize that task-evoked FC changes reflect transient changes in brain network coupling in response to specific task demands.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…At a first glance, this seems inconsistent with previous findings that ELS is associated with decreased amygdala-prefrontal FC during resting state (Burghy et al, 2012;Fan et al, 2014;Herringa et al, 2013). However, it is important to emphasize that task-evoked FC changes reflect transient changes in brain network coupling in response to specific task demands.…”
Section: Discussioncontrasting
confidence: 81%
“…Task-evoked FC changes between amygdala and other limbic-prefrontal regions have been demonstrated during transient acute stress (Hermans et al, 2011;Vaisvaser et al, 2013;Veer et al, 2011). It has also been shown that ELS impacts structural connectivity and trait-like rs-FC within the limbic-prefrontal circuit (Burghy et al, 2012;Fan et al, 2014;Hart and Rubia, 2012;Herringa et al, 2013). Here we hypothesize that ELS influences stress-induced FC changes from amygdala to mPFC and hippocampus.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Other research indicates that (a) behavioral inhibition in infancy predicts structural abnormalities in the ventromedial PFC in young adulthood (Schwartz et al, 2010); (b) early life stress mediates-via increased cortisol levels-decreased functional connectivity between the amygdala and the vmPFC 14 years later (Burghy et al, 2012); and (c) childhood maltreatment portends compromised functional connectivity between the subgenual cingulate cortex and both the amygdala and the hippocampus in adolescence (Herringa et al, 2013). Thus, environmental experience appears to play an important role in the development of neural vulnerability to emotion dysregulation among those with internalizing as well as externalizing disorders.…”
Section: Trait Anxiety Trait Impulsivity and Emotion Dysregulation mentioning
confidence: 99%